Evaluation of Universal Health Coverage (UHC) Policy on Bawean Island, Gresik Regency - Aldana, Shofia; Wibawani, Sri (Universitas Muhammadiyah Ponorogo, 2025)
Health is a basic need for every individual that must be fulfilled. UHC is a condition where all individuals and groups receive health services without being hindered by costs. Law Number 32 of 2004 on Regional Government states that health affairs are mandatory matters under the authority of local governments, including Gresik Regency. The seriousness of Gresik Regency in promoting the realization of UHC can be proven by the implementation of UHC (PBID) based on Gresik Regent Regulation Number 60 of 2022 concerning the Implementation of UHC in the National Health Insurance Program in Gresik Regency. The Gresik Regency Government has launched free health insurance, only requiring the presentation of an ID card and/or family card. Since its implementation, UHC in Gresik Regency has continuously increased, earning a UHC award in 2023. Gresik Regency has a remote area called Bawean Island. The geographical condition of Bawean Island, as an outermost area of Gresik Regency, which is far from the regency center, certainly affects access to health services. The main focus of this research is to conduct an evaluation using Michael Scriven's formative evaluation model, which consists of measuring the periodic implementation results, measuring whether clients or participants are moving towards the desired goals, and measuring whether resources have been used according to plan. This research uses descriptive research with a qualitative approach, collecting data through observation, interviews, and documentation. The research results show that UHC PBID has achieved the UHC objectives stated in Regent Regulation Number 60 of 2022, clients or participants have moved towards the desired goals, but resources have not been used according to plan.